Magnetic nanoparticle stimulation of the nucleus accumbens affects neural activity but not behavior during opioid reinstatement in rats - Gilbert, Ian M. (Tufts University. Tisch Library., 2023)
Research has shown that mechanical vibration of magnetic nanoparticles (MNPs) is able to stimulate neurons. This study expands on preliminary data that suggested MNP stimulation of the nucleus accumbens (NAc) is able to attenuate opioid reinstatement in rats, a model of relapse. Here, MNP stimulation of the NAc was not found to impact behavior during oxycodone reinstatement in rats. However, preliminary data suggest that MNP stimulation of the NAc results in increased activity in the medial prefrontal cortex and has sex-dependent effects on the NAc.; Cummings School of Veterinary Medicine Student Summer Research 2023.